2013
DOI: 10.3233/jad-121786
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of S-Nitrosoglutathione (GSNO) Against Cognitive Impairment in Rat Model of Chronic Cerebral Hypoperfusion

Abstract: Chronic cerebral hypoperfusion (CCH), featuring in most of the Alzheimer's disease spectrum, plays a detrimental role in brain amyloid-β (Aβ) homeostasis, cerebrovascular morbidity, and cognitive decline; therefore, early management of cerebrovascular pathology is considered to be important for intervention in the impending cognitive decline. S-nitrosoglutathione (GSNO) is an endogenous nitric oxide carrier modulating endothelial function, inflammation, and neurotransmission. Therefore, the effect of GSNO trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 66 publications
7
68
0
Order By: Relevance
“…Similar to the role of ONOO − , over accumulations of cellular GSNO and S-nitrosylated proteins (PrSNO) under pathological conditions with the presence of transition metals or GSNO reductase (GSNOR/ADH5) deficient conditions is reported to be harmful for neural and immunological functions [29-31]. However, physiological levels of GSNO/PrSNO are implicated in regulation of various cellular processes for cardiovascular hemodynamics [32], redox balance [33, 34], and inflammatory processes [35, 36]. In addition, the reported beneficial effect of exogenous GSNO treatment in various neurological, cardiovascular, infectious, and immune disease models [22, 36-46] suggest the pathophysiological importance of GSNO-mediated cellular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the role of ONOO − , over accumulations of cellular GSNO and S-nitrosylated proteins (PrSNO) under pathological conditions with the presence of transition metals or GSNO reductase (GSNOR/ADH5) deficient conditions is reported to be harmful for neural and immunological functions [29-31]. However, physiological levels of GSNO/PrSNO are implicated in regulation of various cellular processes for cardiovascular hemodynamics [32], redox balance [33, 34], and inflammatory processes [35, 36]. In addition, the reported beneficial effect of exogenous GSNO treatment in various neurological, cardiovascular, infectious, and immune disease models [22, 36-46] suggest the pathophysiological importance of GSNO-mediated cellular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, GSNO treatment also inhibited the IL-6/TGF-β and IL-23 induced T H 17 cell polarization and their effector function under in vitro cell culture conditions but without affecting T H 1 (IFN-γ) and T H 2 (IL-4) immune responses [22]. Moreover, GSNO was reported to modulates the activities of proinflammatory transcription factors, such as NF-κB, AP-1, and STAT3 [35, 36, 48] and thus modulates gene expression for various proinflammatory effectors, such as ICAM-1, and VCAM-1 [35, 36, 43, 48, 49], as well as endothelial recruitment of peripheral immune cells for their CNS infiltration [36]. Therefore, it is important to understand the role of NO in immune and CNS disease process for MS and EAE.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory described activities of GSNO in neuro- and cognitive-protection using rats subjected permanent bilateral common carotid artery occlusion (pBCCAO) as a model for chronic cerebral hypoperfusion [6]. GSNO treatment also reduced the Aβ load and ICAM- 1/VCAM-1 expression in the brains of pBCCAO rats and increased Aβ uptake by microglia and endothelial cells and decreased neuronal Aβ synthesis by inhibiting activity of BACE1 in in vitro cell culture models [6].…”
Section: Introductionmentioning
confidence: 99%
“…Won et al (61) found that S-nitrosoglutathione palys a protective role against cognitive impairment in rat model of chronic cerebral hypoperfusion. S-nitrosoglutathione is an endogenous nitric oxide carrier modulating endothelial function, inflammation, and neurotransmission.…”
Section: Nitric Oxide Carrier: S-nitrosoglutathionementioning
confidence: 99%